An investigation of the dynamic safety performance of power-assisted bicycles (PABs) - Aehanz Bin Amran (Nanyang Technological University, 2023)
The objective of this project is to investigate the dynamic safety performance of power-assisted bicycles (PABs) in Singapore based on stability and handling tests. The study will be conducted within Nanyang Technological University (NTU). Multiple tests, such as the self-stability test, straight-line test and slalom test, will be conducted on popular PABs in Singapore and conventional big wheel bicycles such as the Montague road bike and a 20” wheel mechanical bike.